Indoor air quality (IAQ) guideline: contribution for portuguese measures - Jesus, L. (2006)
This work intends to create an orientation line for professionals of the construction sector, in a way to guarantee the Indoor Air Quality (IAQ) inside the buildings in Portugal. "Guidelines for the Sustainability" is being prepared and in it, the indoor air quality is considered as one of the most relevant parameters to be characterized. In an evident and didactic way, a guide will be published for architects, engineers and users, with some strategies to be applied in different project phases, from the design phase, through the utilization and up until the demolition phase.